From One Person to Two Person Psychotherapy: Considerations and Practicalities for Including the Partner in the Treatment - Hay, Jonathan (Auckland University of Technology, 2011)
This dissertation explores problems and considerations that arise when individual psychotherapy warrants consideration of the client’s partner, and they are subsequently introduced into the therapy either at the onset or at a later stage in the treatment. A systematic literature review was conducted and themes that emerged include: how individual psychotherapy impacts on the client’s partner; when to consider including the partner in the treatment; varying psychotherapy formats for treating both partners - including changing from individual to couple therapy, and introducing a simultaneous individual or couple therapy; and the advantages and disadvantages of one therapist treating both partners compared to two therapists conducting separate therapies. Although client’s partners are often overlooked or thought of as external factors, there are a variety of options for including them in the treatment.
Keywords: Couple; Relationship; Marital; Psychotherapy; Spouse; Marriage